High Methylmercury in Arctic and Subarctic Ponds is Related to Nutrient Levels in the Warming Eastern Canadian Arctic - MacMillan, Gwyneth A; Girard, Catherine; Chételat, John; Laurion, Isabelle; Amyot, Marc (Environmental science & technology, 2015)
Permafrost thaw ponds are ubiquitous in the eastern Canadian Arctic, yet little information exists on their potential as sources of methylmercury (MeHg) to freshwaters. They are microbially active and conducive to methylation of inorganic mercury, and are also affected by Arctic warming. This multiyear study investigated thaw ponds in a discontinuous permafrost region in the Subarctic taiga (Kuujjuarapik-Whapmagoostui, QC) and a continuous permafrost region in the Arctic tundra (Bylot Island, NU). MeHg concentrations in thaw ponds were well above levels measured in most freshwater ecosystems in the Canadian Arctic (>0.1 ng L(-1)). On Bylot, ice-wedge trough ponds showed significantly higher MeHg (0.3-2.2 ng L(-1)) than polygonal ponds (0.1-0.3 ng L(-1)) or lakes (<0.1 ng L(-1)). High MeHg was measured in the bottom waters of Subarctic thaw ponds near Kuujjuarapik (0.1-3.1 ng L(-1)). High water MeHg concentrations in thaw ponds were strongly correlated with variables associated with high inputs of organic matter (DOC, a320, Fe), nutrients (TP, TN), and microbial activity (dissolved CO2 and CH4). Thawing permafrost due to Arctic warming will continue to release nutrients and organic carbon into these systems and increase ponding in some regions, likely stimulating higher water concentrations of MeHg. Greater hydrological connectivity from permafrost thawing may potentially increase transport of MeHg from thaw ponds to neighboring aquatic ecosystems.